Evaluation and Improvement Recommendations for the Development of an Informal Job Seeker Application Using the Scrum Maturity Model: (Case Study of the ABC Application at PT XYZ) - Salma Salsabila Dwinta; Joko Iskandar (International Journal Software Engineering and Computer Science (IJSECS), 2025)
PT XYZ developed the ABC application to support informal job seekers through Scrum framework implementation during redevelopment. Implementation obstacles including inadequate backlog management, ambiguous Definition of Done (DoD) criteria, and irregular Scrum event execution prevented optimal framework adoption. We assess Scrum practice maturity levels through the Scrum Maturity Model (SMM) while proposing specific enhancement strategies. Our mixed-methods investigation combined KPA-based questionnaires with semi-structured interviews across development teams. Results indicate the project operates at Maturity Level 2 (Managed), achieving an 81.8% average KPA rating. Software Requirements Engineering emerged as the sole Level 2 Key Goal reaching Fully Achieved status (86.25%), whereas goals spanning Levels 3-5 maintained Largely Achieved classifications. Strategic recommendations encompass DoD clarification, enhanced Product Owner engagement, standardized performance metrics implementation (burndown and velocity charts), Sprint Review optimization, and Work in Progress (WIP) limit application. Management validation at PT XYZ resulted in 62.5% recommendation acceptance, revealing that several practices existed pre-assessment yet lacked optimization. The research delivers practical guidance for Scrum adoption enhancement and process maturity advancement, specifically within software development projects serving informal labor markets.